Effects of Employees’ Positive Affective Displays on Customer Loyalty Intentions: An Emotions-as-Social-Information Perspective - Wang, Ze; Singh, Surendra N.; Li, Yexin Jessica; Mishra, Sanjay; Ambrose, Maureen; Biernat, Monica (Academy of Management Journal, 2017)
Employees’ positive affective displays have been widely used as a strategic tool to enhance service experience and strengthen customer relationships. Companies have primarily focused their employee training programs on two dimensions of display: intensity and authenticity. Yet there is limited research on when, how, and why these two dimensions affect customer reactions. Drawing on the emotions as social information (EASI) framework (Van Kleef, 2009), we develop a conceptual model in which display intensity and display authenticity differentially influence customer loyalty by changing customers’ affective reactions and cognitive appraisals. Further, we propose that the relative impact of either dimension depends on customers’ motivation to understand the environment deeply and accurately (i.e., their epistemic motivation). We tested our model in one field study and one laboratory study. Results across these two studies provide consistent support for the proposed model and advance our understanding about how different dimensions of employees’ positive affective displays enhance customer reactions. Thus, findings of this research contribute to knowledge on the interpersonal effects of emotions in customer–employee interactions.